Simulation results of pipe whip impact at 55° angle - Shah, Qasim Hussain; Abid, Hasan M.; Rosli, Adib (IIUM Press, 2011)
The safety of pipe whip is related issue for nuclear power and chemical plants, where pIpes are often used to transport fluids at high pressure and high temperature. Simulation analysis for empty pipe and liquid filled pipe are conducted in this study. The model was made of simple pipe whip system which enables the missile pipe to hit the target pipe at an angle of 55° oblique impact. The simulation setup is done by LS-DYNA which is highly nonlinear transient dynamic finite element analysis using explicit time integration. The results show the defonnation occurred in the pipe whip at different degrees of impacts